2016
DOI: 10.3233/jbr-150111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fruit quality and antioxidant activity of kiwifruit during ripening and after storage

Abstract: BACKGROUND: In the Northern hemisphere kiwifruit harvest time is conditioned by low temperatures occurring during the harvesting season while in Southern Italy minimum temperatures in autumn are high enough to support fruit growth and ripening. OBJECTIVE: To evaluate the influence of delayed harvest time on kiwifruit quality attributes. METHODS: The experiment was carried out in a commercial kiwifruit, 'Hayward', orchard located in Southern Italy. In this area, the conventional harvest time occurs 160 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
4
8
0
Order By: Relevance
“…The AA contents of overmature berries ranged from 17.4 to 131 mg 100 g -1 DW, and were 1.43 to 6.21 times lower compared to fully mature berries of the same genotype (Supplemental Table S1). When considering the dynamics of AA during maturation process, our results are in agreement with data reported for acerola (Vendramini and Trugo, 2000), bilberry (Cocetta et al, 2012), apple (Savikin et al, 2014) and kiwifruit (Gullo et al, 2016) where a decrease in AA content in maturing fruits was observed. The decrease in AA content may be explained by the formation of other compounds (3-hydroxy-2-pyron) as a result of oxidative breakdown of AA (Vendramini and Trugo, 2000) or by a decrease in L-galactono-1.…”
Section: Moisture Contentsupporting
confidence: 92%
“…The AA contents of overmature berries ranged from 17.4 to 131 mg 100 g -1 DW, and were 1.43 to 6.21 times lower compared to fully mature berries of the same genotype (Supplemental Table S1). When considering the dynamics of AA during maturation process, our results are in agreement with data reported for acerola (Vendramini and Trugo, 2000), bilberry (Cocetta et al, 2012), apple (Savikin et al, 2014) and kiwifruit (Gullo et al, 2016) where a decrease in AA content in maturing fruits was observed. The decrease in AA content may be explained by the formation of other compounds (3-hydroxy-2-pyron) as a result of oxidative breakdown of AA (Vendramini and Trugo, 2000) or by a decrease in L-galactono-1.…”
Section: Moisture Contentsupporting
confidence: 92%
“…Diversity of berry phenolics is observed in several ways, including: (i) genetic and environmental factors, such as species and variety, cultivation methods, fertilization, weather, ripeness and harvesting season, conditions and time of storage [51,52,53,54,55,56,57]; (ii) chemical structures, ranging from simple single-aromatic ring compounds to large complex molecules built up from multiple smaller ones [58]; (iii) degree of oxidation and substitution patterns of hydroxylation; (iv) abilities to exist as stereoisomers; (v) glycosylation by sugar moieties and other substituents; and (vi) conjugation to form polymeric molecules [59].…”
Section: Bioactive Compound Profile and Antioxidant Capacity Of Bementioning
confidence: 99%
“…Whereas the specific composition of berry fruits depends besides by the species, the variety, degree of ripeness, as well as environmental and climatic conditions [15,25,26], the aim of this study was to evaluate the nutraceutical proprieties of wild and cultivated blackberry and wild elderberry fruits produced in some regions of Southern Italy, such as Basilicata and Campania.…”
Section: Introductionmentioning
confidence: 99%